Identification of biological-active compounds in somatic callus cultures in Plantago major - Jiménez-Quesada, Karol (2017)
With growing interest in the use of the properties of medicinal plants, the study of bioactive compounds thereof becomes a field of exciting new research, which seeks to relate and understand the synergy between natural substances and their positive impact on human health. An important utility of establishing cell cultures is precisely that they offer the opportunity to analyze the biochemical level industrial or clinical use having a given species due to the presence of certain compounds in their bodies with the ability to produce them at the cellular level and in vitro. In this work the induction of somatic callus formation from seed germination og Plantago major wasachieved in vitro, which were disinfected using a previously established protocol. Then leaf explants (1.0-1.5 cm2) of plants were taken vitro and cultured in semi-solid medium (M&S), for which a matrix of 28 treatments combining different concentrations of growth regulators (2,4-D and TDZ) in M&S medium. From this matrix 3 medium cultures (M14, M27 and M28) with the best results in the induction of callus formation as somatic embryogenesis were selected. For identification and quantification of bioactive compounds present in the extracts lyophilized callus analysis of two standards were performed to test their effectiveness as chemical markers in quantifying verbascosides and iridoids aucubin based on P. major. Hydro-alcoholic extracts of raw P. major, were prepared according to the protocols established by the company Laboratorios Lisan. They were prepared at a concentration of 10% w/v using 95% ethanol. With HPLC analysis for both markers signals with stable baseline and good resolution they were generated, being the most effective of verbascóside, so we continued with the evidence necessary to achieve establish a protocol of quantification in extracts from corns established. The established methodology for the detection and quantification of bioactive metabolites in this system can be refined based on an extraction solvent that gives stability to the extracts in a determined time period.